Germline cancer susceptibility gene variants, somatic second hits, and survival outcomes in patients with resected pancreatic cancer - Yurgelun, Matthew B. (Genet Med, 2018)
PURPOSE: Germline variants in double-strand DNA damage repair (dsDDR) genes (e.g., BRCA1/2;) predispose to pancreatic adenocarcinoma (PDAC) and may predict sensitivity to platinum-based chemotherapy and PARP inhibitors. We sought to determine the prevalence and significance of germline cancer susceptibility gene variants in PDAC with paired somatic and survival analyses. METHODS: Using a customized next-generation sequencing panel, germline/somatic DNA was analyzed from 289 patients with resected PDAC ascertained without preselection for high-risk features (e.g., young age, personal/family history). All identified variants were assessed for pathogenicity. Outcomes were analyzed using multivariable-adjusted Cox proportional hazards regression. RESULTS: 28/289 (9.7%; 95% CI 6.5%−13.7%) patients carried pathogenic/likely pathogenic germline variants, including 21 (7.3%) dsDDR gene variants (3 BRCA1, 4 BRCA2, 14 other dsDDR genes [ATM, BRIP1, CHEK2, NBN, PALB2, RAD50, RAD51C)], 3 Lynch syndrome, and 4 other genes (APC p.I1307K, CDKN2A, TP53). Somatic sequencing and immunohistochemistry identified second hits in the tumor in 12/27 (44.4%) patients with germline variants (1 failed sequencing). Compared to non-carriers, patients with germline dsDDR gene variants had superior overall survival (HR 0.54; 95% CI 0.30–0.99; P=0.05). CONCLUSION: Nearly 10% of PDAC patients harbor germline variants, although the majority lack somatic second hits, the therapeutic significance of which warrants further study.